Abnormal electrocardiographic findings in athletes: recognising changes suggestive of cardiomyopathy - Drezner, J. A.; Ashley, E.; Baggish, A. L.; Börjesson, M.; Corrado, D.; Owens, D. S.; Patel, A.; Pelliccia, A.; Vetter, V. L.; Ackerman, M. J.; Anderson, J.; Asplund, C. A.; et al. (British Journal of Sports Medicine, 2013)
Cardiomyopathies are a heterogeneous group of heart muscle diseases and collectively are the leading cause of sudden cardiac death (SCD) in young athletes. The 12-lead ECG is utilised as both a screening and diagnostic tool for detecting conditions associated with SCD. Fundamental to the appropriate evaluation of athletes undergoing ECG is an understanding of the ECG findings that may indicate the presence of an underlying pathological cardiac disorder. This article describes ECG findings present in cardiomyopathies afflicting young athletes and outlines appropriate steps for further evaluation of these ECG abnormalities. The ECG findings defined as abnormal in athletes were established by an international consensus panel of experts in sports cardiology and sports medicine.